2005
DOI: 10.1111/j.1467-9590.2005.01549
|View full text |Cite
|
Sign up to set email alerts
|

Compressible Modes of the Rotating‐Disk Boundary‐Layer Flow Leading to Absolute Instability

Abstract: This work is devoted to the clarification of the viscous compressible modes particularly leading to absolute instability of the three-dimensional generalized Von Karman's boundary-layer flow due to a rotating disk. The infinitesimally small perturbations are superimposed onto the basic Von Karman's flow to achieve linearized viscous compressible stability equations. A numerical treatment of these equations is then undertaken to search for the modes causing absolute instability within the principle of Briggs-Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, we shall concentrate on a more ideal fluid here and use σ = 0.72 throughout in the subsequent analysis. Despite the fact that the selection of the Prandtl number has an influence on the linear and viscous absolutely unstable modes (see for instance [43]), the use of 0.72 as opposed to 1 is believed to have little quantitative effect on our high Reynolds number convective instability results. Two more points are worthy of consideration here.…”
Section: Problem Formulationmentioning
confidence: 94%
“…However, we shall concentrate on a more ideal fluid here and use σ = 0.72 throughout in the subsequent analysis. Despite the fact that the selection of the Prandtl number has an influence on the linear and viscous absolutely unstable modes (see for instance [43]), the use of 0.72 as opposed to 1 is believed to have little quantitative effect on our high Reynolds number convective instability results. Two more points are worthy of consideration here.…”
Section: Problem Formulationmentioning
confidence: 94%
“…The resonance mechanism that results from the coalescence of two eigenmodes having zero group velocity and also initially originating from the distinct wavenumber planes in the instability field is known as the absolute instability. This mechanism is well-documented in the literature for a non-conducting Von Kármán flow; see for instance [3][4][5] amongst many others. Moreover, the recent work of Jasmine and Gajjar [6] concluded that the presence of a normal magnetic field acts in the way of stabilizing the absolute instability mechanisms.…”
Section: Introductionmentioning
confidence: 92%
“…The disturbance components of the above system are determined later by solving the form of the Navier-Stokes equations that results from substituting these quantities in (1)(2)(3)(4)(5)(6), and subtracting out the mean flow equations, satisfying (8)(9). Having linearized the equations for small perturbations, we find that the linearized Navier-Stokes operator has coefficients independent of θ , and hence, the disturbances can be decomposed into a normal mode form proportional to e iR(βθ−ωt) .…”
Section: Linear Stability Equationsmentioning
confidence: 98%
“…This instability was first explored by [9][10][11] and [12]; see also the recent study of [13]. Making use of the Briggs-Bers criterion and assuming that the flow is parallel, the latter authors were able to show that the flow becomes both inviscidly and viscously absolutely unstable.…”
Section: Introductionmentioning
confidence: 96%